Gender Disparity in It- and Stem-Professions: Analysis of Key Factors - M. Yu. Varavva (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
The article focuses on the problem of professional integration of Russian women in new processes of information and technological development. The topic of gender inequality on labour market in certain shapes and forms is typical of nearly all today’s professions. The sphere of information and digital technologies is not an exception. IT- and STEM-industries present only one line in a vast scope of research dealing with women inclusion in this professional field. The author studies reasons for underestimation of labour and creative potential of women, due to which women find themselves connected with humanitarian and social occupations, while men – with occupations dealing with mathematics, engineering, high technologies and information science. It was pointed out that various professional skills, talents and creative dominance of women are not in demand. A whole set of external and internal factors were investigated that prevent women from entering professional spheres of IT and STEM, which can back up gender disparity and segregation in labour sphere. The author came to the conclusion that gender disparity not only exercises a negative impact on social and ethic relations but can cause direct economic and staff costs for the country. In its turn the extended presence of women in new digital industries and technical sectors can foster the development of economy and at the same time can help resolve numerous problems of gender inequality in labour sphere. Attaining gender balance is still an open and multi-sided topic in theoretical and practical plan on the junction of investigating labour economics and sociology of labour relations.